Effect of aluminizing and oxidation on the thermal fatigue damage of hot work tool steels for high pressure die casting applications. (February 2019) - Salem, M.; Le Roux, S.; Dour, G.; Lamesle, P.; Choquet, K.; Rézaï-Aria, F.
Highlights: Environment effects on Thermal Fatigue (TF) damage of X38CrMoV5 steel are studied. TF loadings induce a heat checking network on intermetallic or compact oxide layer. Micro-crack density is controlled by mechanical properties of the superficial layer. Heat-checking is the main factor determining the premature cracking of the steel. The crack propagation mechanisms are assisted by oxidation at high temperature. Abstract: The interaction between thermal fatigue and aluminizing and/or oxidation is investigated using an experimental approach based on decoupling of mechanisms. Virgin and pre-aluminized steel specimens are tested in air and nitrogen between 100 and 650 °C. Homogeneous uniaxial micro-crack network forms on the oxidised or pre-aluminized surface in air, with a better resistance to micro-cracking for the intermetallic coating. The propagation of the micro-cracks is delayed in nitrogen, whilst no evidence of micro-cracking is observed on the virgin specimen. The premature cracking of the steel depends on the formation of the superficial micro-crack network, and the crack propagation is assisted by oxidation.